Đặc điểm trầm tích cắc mặt cắt Đệ Tam vùng Tây Bắc Việt Nam - Huyên, Nguyễn Xuân; Pha, Phan Đông; Hưng, Nguyễn Quang (Vietnam Journal of Earth Sciences, 2006)
Characteristics of Tertiary sedimentary crosssections in Northwestern Vietnam